GENETIC ALGORITHM OPTIMIZED PACKET FILTERING - NURIKA, OKTA (2013)
n our research, we present a method to optimize packet filtering by genetic algorithm. Packet filtering in our work consists of packet capturing and firewall rules reordering. Genetic algorithm is used to automate rules reordering and the discovery of optimal combination of packet capture configuration, in the framework of PF_RING platform and rules ordering. Our method has been tested in different sizes of network traffic load. Genetic Algorithm evolves configuration based on the recorded throughput rates; the higher the throughput the better the solution. Results obtained indicate the effectiveness ofthe approach.